Detection, Identification and Molecular Characterization of the 16SrII-V Subgroup Phytoplasma Strain Associated with Pisum sativum and Parthenium hysterophorus L - Chiu, Yi-Ching; Liao, Pei-Qing; Mejia, Helen Mae; Lee, Ya-Chien; Chen, Yuh-Kun; Yang, Jun-Yi (Plants (Basel), 2023)
Two unrelated plant species, green pea and parthenium weed, harboring typical phytoplasma symptoms, were discovered in Yunlin, Taiwan. Green pea (Pisum sativum.) and parthenium weed (Parthenium hysterophorus L.) are both herbaceous annual plants belonging to the Fabaceae and Asteraceae families, respectively. Displayed symptoms were witches’ broom, phyllody and virescence, which are typical indications of phytoplasma infection. Pleomorphic phytoplasma-like bodies were observed under the transmission electron microscope in the sieve elements of symptomatic green pea and parthenium weed. The iPhyClassifier-based virtual RFLP study demonstrated that the phytoplasma associated with the diseased plants belongs to the 16SrII-V subgroup. The disease symptoms of both plants can be explained by the identification of PHYL1 and SAP11 effectors, identical to those of peanut witches’ broom phytoplasma. The phytoplasma strains identified in this study present a very close phylogenetic relationship with other 16SrII-V subgroup phytoplasma strains discovered in Taiwan. These results not only convey the local status of the 16SrII-V subgroup phytoplasma strains but also encourage attention to be given to preventing the spread of this threat before it becomes pervasive.